Translation, Book and Colporteurs in the Spread of Protestant Mission in Anatolia (1850-1900) - Asoğlu, İsmail (Fırat University, 2024)
In the XIXth century, colporteurs had a great share in the intellectual and spiritual evolution of Ottoman Protestants. This was a priority task for the educational organization of the missionaries. Especially, the works published in the Istanbul American Bible House transported to cities and villages in Anatolia through colporteurs promoting the publication of books from chemistry to mathematics, natural philosophy to ethics were indicators of Protestant missionary work improvement. While the distribution of the Torah or Bible did not cause issues for the state, works highlighting sectarian differences were considered objectionable. The study emphasizes transformative effects of translation, book sales and distribution on Anatolian Christians between 1850 and 1900, which have a significance in terms of missionary work, beside comparing the policy of Protestant missionaries with the reform efforts of the Ottoman Empire. The memoirs and reports of the missionaries, "Missionary Herald" bulletins, and the correspondence between the center and local administrations in the Ottoman Archives provide rich data for understanding the process.

XIX. yüzyılda; Osmanlı Protestanlarının entelektüel ve manevi tekâmülünde, misyoner kitap satıcı ve dağıtıcılarının payı büyüktü. Bu iş, misyonerliğin eğitim yapılanması açısından öncelikli görevler arasında yer alıyordu. Bilhassa İstanbul American Bible House’da basılan eserler, seyyar kitapçılar sayesinde Anadolu’nun birçok şehir ve köylerine taşındı. Kimyadan matematiğe, doğa felsefesinden ahlak biliminin unsurlarına ilişkin kitap basımının artışı, Protestan misyonerliğinin gelişim göstergelerinden biriydi. Devlet için Tevrat ya da İncil’in dağıtımı sorun yaratmazken, mezhebî farklılıkları öne çıkaran eserlerin, özellikle cami ve medrese civarında satım ve dağıtımı sakıncalı görülmüştü. Misyonerlik açısından merkezi bir yere sahip tercüme, kitap satım ve dağıtımı, bu alandaki çabaların anlaşılması bakımından önem arz eder. Bu nedenle çalışma, 1850-1900 yılları arasında, işlevsel olarak tercümenin, kitap satım ve dağıtımının Anadolu Hristiyanları üzerindeki somut dönüştürücü etkilerine odaklanmaktadır. Protestan misyonerliğinin bu siyaseti, Osmanlı Devleti’nin reform çabalarıyla karşılaştırmalı olarak ele alınmayı gerektirmektedir. Misyonerlerin hatırat ve raporları, Osmanlı sahasındaki faaliyetlerinin yayımlandığı “Missionary Herald” bültenleri ile Osmanlı Arşivlerindeki merkez ile yerel idareler arası yazışmalar sürecin anlaşılması adına zengin veriler sunmaktadır.
PROTESTAN MİSYONERLİĞİNİN ANADOLU’DAKİ YAYILIMINDA TERCÜME, KİTAP VE SEYYAR KİTAPÇILAR (1850-1900)
Keywords: Historical; Comparative and Typological Linguistics; Tarihsel; Karşılaştırmalı ve Biçimsel Dilbilim